3(x+3)+12=6x+3

Simple and best practice solution for 3(x+3)+12=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+3)+12=6x+3 equation:


Simplifying
3(x + 3) + 12 = 6x + 3

Reorder the terms:
3(3 + x) + 12 = 6x + 3
(3 * 3 + x * 3) + 12 = 6x + 3
(9 + 3x) + 12 = 6x + 3

Reorder the terms:
9 + 12 + 3x = 6x + 3

Combine like terms: 9 + 12 = 21
21 + 3x = 6x + 3

Reorder the terms:
21 + 3x = 3 + 6x

Solving
21 + 3x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
21 + 3x + -6x = 3 + 6x + -6x

Combine like terms: 3x + -6x = -3x
21 + -3x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
21 + -3x = 3 + 0
21 + -3x = 3

Add '-21' to each side of the equation.
21 + -21 + -3x = 3 + -21

Combine like terms: 21 + -21 = 0
0 + -3x = 3 + -21
-3x = 3 + -21

Combine like terms: 3 + -21 = -18
-3x = -18

Divide each side by '-3'.
x = 6

Simplifying
x = 6

See similar equations:

| 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= | | (3x+39/8)=0 | | 7k-2(3k+1)= | | 5x-1+x=15 | | 11=((7w-9)/2)+((8w+1)/5) | | y/8+4=6 | | 9(2/3+x)=24 | | 4x+9=8-6x | | 18-.10x=34 | | 3[7r-7]=-6+6r | | 7n-5n=9(n+7)-7(n+10) | | -5x1/4x4 | | -2/8n=3 | | 5n-3=3n-55 | | m/2=-9 | | 6x-17=11x+10 | | 12y+4=9y-5 | | 59-(G/2)=54 | | -(10x-10)=5(6x-6) | | (x-4)(5x-2)-3(x-4)=0 | | 14+(8/n)=16 | | -2=n/7-4 | | 3t-10+9=17+4t-3 | | -1=-6+b/4 |

Equations solver categories